PENGARUH UKURAN FISIK DAN JUMLAH UMBI PER LUBANG TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) - Yenny Sufyati (Jurnal Floratek, 2006)
The Influence of Physical Size and Number of Bulbs Per Hole on Growth and Yield of Shallot (Allium ascalonicum L.)  Yenny Sufyati, Said Imran AK, dan FikrindaABSTRACTThe Influence of Physical Size and Number of Bulbs Per Hole on Growth and Yield of Shallot (Allium ascalonicum L.)              The objective of this study is to find out the influence of bulb physical size and the suitable number of the bulb per hole in order to increase the growth and yield of shallot.  The result showed that the bulb size gave no significant differences of the plant height at 15 days after planting, but it had given the very significant differences at 30 and 45 days.  Moreover, the highly significant differences are also shown at the number of leaves at 45 days after planting, the number of bulb per cluster, the weight of the wet and dried plant per netto plot and the weight of the dried bulb per netto plot.  All parameters of the growth and yield plant evaluated were significantly affected by the number of bulb per hole.  There were highly significant interaction between the bulb physical size and the number of bulb per hole on the plant height at 30 days after planting, the number of leaves at 45 days after planting and the number of bulb per cluster.  In general, treatment U1 gave the growth and yield of plant better than treatment U2 and U3.  In addition, three bulbs per hole (J3) had better effect on the growth and yield of plant than other treatments.